2015
DOI: 10.1021/acsami.5b10373
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion Synthesis of Size-Tunable CH3NH3PbBr3 Quantum Dots: An Alternative Route toward Efficient Light-Emitting Diodes

Abstract: We report a facile nonaqueous emulsion synthesis of colloidal halide perovskite quantum dots by controlled addition of a demulsifier into an emulsion of precursors. The size of resulting CH3NH3PbBr3 quantum dots can be tuned from 2 to 8 nm by varying the amount of demulsifier. Moreover, this emulsion synthesis also allows the purification of these quantum dots by precipitation from the colloidal solution and obtains solid-state powder which can be redissolved for thin film coating and device fabrication. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
361
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 437 publications
(375 citation statements)
references
References 28 publications
8
361
1
1
Order By: Relevance
“…This superior characterization is similar as the shelling of ZnS around CdSe QDs core, photoexcitated carriers would be confined, and a high PL quantum efficiency could be expected. For a further confirmation, Zhong and coworkers performed the energy-dispersive spectroscopy measurements for synthesized MAPbBr 3 QDs [20]. They found a Br/Pb ratio of 3:5 for QDs with an average diameter of 3.3 nm, matching with the observation in Li's report.…”
Section: Synthesis Of Mapbx 3 Qdssupporting
confidence: 65%
See 1 more Smart Citation
“…This superior characterization is similar as the shelling of ZnS around CdSe QDs core, photoexcitated carriers would be confined, and a high PL quantum efficiency could be expected. For a further confirmation, Zhong and coworkers performed the energy-dispersive spectroscopy measurements for synthesized MAPbBr 3 QDs [20]. They found a Br/Pb ratio of 3:5 for QDs with an average diameter of 3.3 nm, matching with the observation in Li's report.…”
Section: Synthesis Of Mapbx 3 Qdssupporting
confidence: 65%
“…For instance, Huang et al reported the emulsion-based synthesis of perovskite nanocrystals involving many morphologies at RT [20]. Li et al reported that the CsPbX 3 QDs can be synthesized at RT, which was similar to the ligand-assisted reprecipitation method used for MAPbX 3 QD system [19].…”
Section: Synthesis Of Cspbx 3 Qdsmentioning
confidence: 99%
“…Methods such as emulsion synthesis 49 and electrospray technique coupled antisolvent − solvent extraction 50 have been used for the synthesis of perovskite NCs of different morphologies, mostly yielding rather polydisperse nanoparticles. It has been shown that nearly Colloidal lead halide perovskite nanocrystals H Huang et al monodisperse blue-emitting nanoplatelets and green-emitting nanorods can be prepared in 1-octadecene at high temperature.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
“…For instance, Huang et al 49 reported the emulsion-based synthesis of perovskite NCs (both hybrid and all-inorganic) at room temperature. In a recent report Li et al 64 Figure 5 showed that CsPbX 3 NCs can be synthesized at room temperature, similar to the LARP method used for the MAPbX 3 system.…”
Section: (Figures 4f-h) the Initially Formed Cubic Ncs Transformed Intomentioning
confidence: 99%
“…Early demonstrations of perovskite LED (PeLED) using polycrystalline films suffer from low external quantum efficiency (EQE) due to nonideal PLQY of the bulk halide perovskites, while PNCs present potential alternatives toward efficient and bright light-emitting devices. [52][53][54][55][56][57] …”
Section: Introductionmentioning
confidence: 99%